(untitled) (Majalah Kedokteran Bandung, 2023)
Patellar clunk crepitation is a well-known complication following knee replacement surgery and is associated with posterior stabilized knee replacement surgery and surgical technique. Currently, patellar clunk or crepitation management following knee replacement surgery with preserved patella remains unclear. The purpose of this case report is to discuss whether patellar clunk or crepitation management should include debridement with patellar resurfacing or debridement alone. This case describes a patellar crepitation after knee replacement surgery with the preserved patella. The surgery went uneventfully using the standard medial parapatellar approach. However, the patient was still unsatisfied with the chronic left knee pain (>3 months) and crepitation that developed following the surgery, and the patient was diagnosed with patellar clunk and crepitation (PCC). A patellar resurfacing procedure was performed with a satisfactory clinical outcome. Replicating the original joint line level and placing the tibial component posteriorly play a pivotal role in preventing PCC. Debridement and patellar resurfacing procedures are recommended in this type of case to overcome the valgus knee alignment and the placement of the tibial component.